An analysis of children’s traumatism in the Republic of Uzbekistan - Rakhmanov, Ruzimboy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
The article analyses children’s traumatism in Uzbekistan within 2000-2009. The authors characterize the organization of prophylaxis, particularly primary and secondary ones, and describe the structure of children’s traumatism by kinds of injuries. A reduction of traumatism in children and an improvement of the aid rendering service during the above period are shown.